Symptomatic Isolated Celiac Artery Dissection following Blunt Trauma - Sang Bong Lee; Hyuk Jae Jung; Jae Hun Kim (Journal of Acute Care Surgery, 2019)
An isolated splanchnic artery injury due to blunt trauma occurs rarely because abdominal vascular injuries are typically associated with injuries to the surrounding abdominal structures, including solid organs or hollow viscus. Of the major abdominal vessels, the celiac artery is the least commonly injured by penetrating or blunt abdominal trauma. Furthermore, a celiac artery dissection due to blunt trauma is rarely reported and there is no clearly defined treatment method, even though endovascular and conservative treatments are accepted widely. On the other hand, endovascular treatment can be challenging if the celiac artery dissection involves its main branch, including the proper hepatic artery, left gastric artery, and splenic artery. This case study presents the treatment experience of a celiac artery dissection involving its main branch following dorsal blunt trauma. Furthermore, conservative treatment is proposed as a treatment option for this rare injury.